A novel biallelic variant in the Popeye domain‐containing protein 1 (POPDC1) underlies limb girdle muscle dystrophy type 25. Issue 2 (17th October 2022) - Mahmood, Arif; Samad, Abdus; Shah, Abid Ali; Wadood, Abdul; Alkathiri, Afnan; Alshehri, Mohammed Ali; Alam, Mohammad Zubair; Hussain, Taimur; He, Pei; Umair, Muhammad
Abstract: POPDC1 also known as BVES, is a highly conserved transmembrane protein, important for striated muscle function and homeostasis. Pathogenic variants in the POPDC1 gene are associated with limb‐girdle muscular dystrophy type 25 (LGMDR25). In the present study, we performed trio‐whole exome sequencing (WES) followed by Sanger sequencing on a single family having LGMD clinical features. Protein modeling of all POPDC1 missense variants (POPDC1 Pro134Leu, POPDC1 Ile193Ser, and POPDC1 Ser201Phe ) associated with LGMDR25 were performed using Molecular Dynamics (MD) simulation. We identified a homozygous missense variant (c.401C>T; p.Pro134Leu) in the POPDC1 gene. Altered 3D structure, disruptive fluctuation, less compactness, and instability were observed in all the three variants of POPDC1 protein models. In comparison, POPDC1 Ser201Phe protein dynamics were more unstable than other variants. Functional study of newly identified variant would add key answers to underlying mechanisms of the disease. Abstract : By WES, we identified a novel pathogenic variant (Pro134Leu) in POPDC1 underlying LGMDR25. Protein Modeling revealed abnormal behavior and instability by all variants found in POPDC1 gene.